Parametric Analysis of Position and Direction of Laminated Composite C-Spar on Aeroelastic Flutter in Aircraft Tail - Ahmad Reza Ghasemi; Hamid Rabieyan-Najafabadi; Hossein Nejatbakhsh; Amin Gharaei (Mechanics of Advanced Composite Structures, 2024)
The aeroelastic stability of the tail is significantly challenged by flutter instability. Skin and spars strongly affect flutter speed due to their torsional and bending stiffness, respectively. C-section spars are primarily utilized in composite structures due to their straightforward manufacturing process. This research aims to investigate the impact of the position and orientation of a laminated composite C-spar on the flutter speed of the airfoil section, utilizing a two-degree-of-freedom flutter method. The position of the C-spar varies between 10% and 50% of the chord length from the leading edge of the airfoil section, while the orientation of the C-spar with respect to the leading edge or trailing edge is also examined. To ensure comparability, the elastic section modulus and mass of the composite spar are maintained nearly constant. When it comes to the structural design process, one of the key challenges is determining the flutter and divergence speeds. In a novel approach, Finite Element Method (FEM) is utilized to calculate the torsional and bending stiffness values. This method provides a more accurate and efficient way to evaluate these important parameters. The results indicate that the location design of the C-spar exerts a more substantial influence on the flutter speed than the orientation of the spar. Furthermore, it is crucial to consider the nonlinear effects of the spar's position and direction in comprehending the aeroelastic instability of the aircraft tail. Additionally, the study found that the addition of a spar to a hollow section of the V-tail does not significantly enhance aeroelastic behavior. Only a modest increase of approximately 20% in flutter speed was observed. The primary effect of the spar lies in the bending stiffness, which does not lead to a substantial increase in flutter speed. Moreover, while flutter occurs before divergence, there can be a considerable distance between the respective speeds. Moving the spar from the leading edge to the mid-chord can reduce this margin, potentially compromising stability. Results show when the C-par position is close to the center of the airfoil, the flutter and divergence speed increase.